Tendencies of Possibility: A Peircean Consideration of Kauffman's Cosmic Mind. Issue 1 (2nd January 2016) - Graves, Mark
ABSTRACT: Stuart Kauffman speculatively proposes a panpsychic interpretation of quantum mechanics, where a cosmic mind makes measurements to change quantum possibilities into classical actuals. However, in response, Charles S. Peirce's understanding of existence simplifies Kauffman's triadic ontology and accounts for an evolving cosmos. Peirce's objective idealism confirms possibility as fundamental to ontological existence, clarifies actuality as specifically related to space-time's extent, and revises Kauffman's broad panpsychism to a narrow but pervasive role for law-like, dispositional tendencies. Theological implications include bridging Arthur Peacocke's Divine Becoming with a neo-Aristotelian, scientifically plausible potential for existence.